Effects of CoO and Bi2O3 single/dual sintering aids doping on structure and properties of Ce0.8Nd0.2O1.9. Issue 14 (1st October 2020) - Chen, Xu; Sun, Xi; Zhou, Jing; Zhou, Defeng; Xiaofei Zhu,; Meng, Jian
Abstract: Nd0.2 Ce0.8 O3-δ (NDC) is one of the most common solid electrolyte materials used in solid oxide fuel cells (SOFCs). However, the densification temperature of NDC electrolyte is above 1400 °C. In this work, Bi2 O3 and CoO sintering aids were individually or synergistically added to Nd0.2 Ce0.8 O3-δ (NDC) electrolytes through the sol-gel method to lower its sintering temperature. Effects of Bi2 O3 -CoO dual sintering aid on the sintering behavior, phase composition, microstructure, and electrochemical properties of NDC electrolyte were all investigated. The data revealed that Bi2 O3 -CoO dual-sintering aid doped-NDC (labeled as NDC-CB) possessed high density and superior conductivity at low temperatures, better than that of Bi2 O3 or CoO single sintering aid. NDC electrolyte doped with Bi2 O3 -CoO dual-sintering aid achieved highest relative density of 95.3% at 1100 °C and total conductivity of 5.765 × 10 -2  S cm -1 at 800 °C. Furthermore, NDC-CB displayed excellent physical and chemical compatibility with La0.6 Sr0.4 Co0.8 Fe0.2 O3-δ (LSCF) cathode and NiO-NDC anode. Oxygen reduction reaction at LSCF/NDC-CB interface was improved by about 40% when compared to NDC. In sum, Bi2 O3 -CoO looks promising as dual-sintering additive for lowing sintering temperature and increasing electrical conductivity of NDC. Therefore, NDC-CB might be potential electrolyte for future intermediate-temperature solid oxide fuel cells (IT-SOFCs). Highlights: The density and properties of NDC samples with sintering aids were improved. NDC with Bi2 O3 -CoO dual-sintering aid exhibited the excellent performance. Dual-sintering aid enhancement was superior to single sintering aids. NDC co-doped with Bi2 O3 -CoO achieved the highest relative density of 95.3%. The total conductivity of NDC-CB was 5.765 × 10 -2  S cm -1 at 800 °C. [1–24 ].